Ukraine’s trade relations with the Middle East and North Africa - Duginets, Ganna; Omran, Hossain Zolfali (WUNU, 2022)
Ukraine’s foreign trade is being restructured and geographically diversified. The countries of the Middle East and North Africa play a key role in these processes in their capacity as trade partners. Consistent revenues from export are especially important for Ukraine’s recovery post-war, so the development of its foreign trade should entail a change in the approach to the Middle East and North Africa, namely a shift away from «casting a wide net» towards more targeted identification of emerging markets and concentrated efforts to deepen trade ties with these select countries. The research outcomes substantiate a comprehensive scientific and methodological approach to assessing the effectiveness of trade cooperation between countries. The proposed approach uses economic and mathematical modelling based on cluster analysis of existing cooperation features to benchmark the conditions of trade cooperation. Based on obtained results, it also allows for a continuous monitoring and assessment of the efficiency of implemented measures geared towards developing trade relations with the countries of the region.
Keywords: international trade; Middle Eastern countries; African countries; export; import; cluster analysis